HUBUNGAN ANTARA PERSEPSI TERHADAP POLA ASUH DEMOKRATIS AYAH DAN IBU DENGAN PERILAKU DISIPLIN REMAJA - Istianah A Rahman (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
This research is aimed to define the relationship bet-ween perception to democracy of the father and mother parenting style with adolescence’s discipline behaviour. The method of data collecting that used is the scale of adolescence’s perception to democracy of the father parenting style, the scale of adolescence’s perception to demo-cracy of the mother parenting style, and the scale of adolescence’s discipline behaviour. All of the scales used by Likert Scale Model consists of four alternative responses. The data analysis is used by regression analysis technique. The result of the research indicated that: (1) there is significant and positive correlation between adoles-cence’s perception to democracy of the father and mother parenting style with adolescence’s discipline behaviour, (2) there is significant and positive correlation between adolescence’s perception to demo-cracy of the father parenting style with adolescence’s discipline beha-viour, (3) there is significant and positive correlation between adoles-cence’s perception to democracy of the mother parenting style with adolescence’s discipline behaviour. The conclusion of this research that the alternative hypothesis is accepted.